2023
DOI: 10.1523/eneuro.0360-22.2023
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Condition-Dependent Changes in Ciliary GPCR Localization in the Brain

Abstract: Primary cilia are cellular appendages critical for diverse types of singling. They are found on most cell types, including cells throughout the central nervous system. Cilia preferentially localize certain G protein-coupled receptors (GPCRs) and are critical for mediating the signaling of these receptors. Several of these neuronal GPCRs have recognized roles in feeding behavior and energy homeostasis. Cell and model systems likeC. elegansandChlamydomonashave implicated both dynamic GPCR cilia localization and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 55 publications
1
15
0
Order By: Relevance
“…Primary cilium elongation could potentially alter the density of signalling molecules present in the primary cilium, thereby affecting downstream signalling (Macarelli et al 2023). Interestingly, it has been suggested that not only the regulation of primary cilium length but also the modulation of ciliated cell rate and receptor localization changes under different physiological conditions in the brain (Brewer et al 2023). Cilium length regulation may be involved in the control of C3-positive reactive astrocyte induction by modulating immune signalling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Primary cilium elongation could potentially alter the density of signalling molecules present in the primary cilium, thereby affecting downstream signalling (Macarelli et al 2023). Interestingly, it has been suggested that not only the regulation of primary cilium length but also the modulation of ciliated cell rate and receptor localization changes under different physiological conditions in the brain (Brewer et al 2023). Cilium length regulation may be involved in the control of C3-positive reactive astrocyte induction by modulating immune signalling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Primary cilium elongation could potentially alter the density of signalling molecules present in the primary cilium, thereby affecting downstream signalling (21). Interestingly, it has been suggested that not only the regulation of primary cilium formation but also the modulation of cilium length, formation rate, and receptor localization changes under different physiological conditions in the brain (39). Cilium length regulation may be involved in the control of A1 astrocyte differentiation by modulating immune signalling pathways.…”
Section: Discussionmentioning
confidence: 99%
“… 65 With advancements in proximity-labeling technologies, it is now possible to consistently isolate and analyze proteins selectively localized to primary cilia. 26 , 66 Studies show that the composition of cilia can be dynamic 26 , 67 and clearly differs between cell types. For example, adenylate cyclase 3 is present in neuronal cilia but has been shown to fail to be detected in IMCD3 kidney cells.…”
Section: Discussionmentioning
confidence: 99%